The switching of friction pairs in "kvazibezznosnyy" state - Бабак, В.П.; Філоненко, С.Ф.; Стадниченко, В.М. (Proceedings of National Aviation University (archive), 2006)
In the work, the results of researches of loading effect on velocity and thickness of the metallic-ceramic layer formation, which is formed as a result of applying the tryboretrofitting mixes in lubrication are presented. It is shown that the maximum rate of growth and the thickness of the metallic-ceramic layer takes place at the peak loads.